Competing in Engineering Design – the Role of Virtual Product Creation - Stark, R.; Krause, F. L.; Kind, C.; Rothenburg, U.; Müller, P.; Stöckert, H. (Cranfield University Press, 2009)
Product creation is facing the next level of fundamental changes. Global demands are growing substantially to achieve energy efficient and sustainable value creation networks for products, production and services without compromising traditional success factors such as time to market, cost and quality. To stay competitive within such an environment development partners in industry and public sectors will require new interplay solutions for engineering design execution, domain knowledge representation, expert competence utilization and digital assistance systems. This scenario offers the chance for virtual production creation solutions to become critical for the future by offering unique engineering capabilities which have not yet explored or deployed. The paper investigates key elements of modern virtual product creation – such as agile process execution, functional product modeling and context appropriate information management – towards their competitive role in satisfying increasing numbers of product requirements, in delivering robust systems integration and in ensuring true sustainable product lifecycle solutions.
Organised by: Cranfield University
Keywords: Virtual Product Creation; engineering design; digital technologies; information and competence management; sustainability, systems integration; process execution